2009
DOI: 10.1042/bj20081402
|View full text |Cite
|
Sign up to set email alerts
|

PIASy inhibits LRH-1-dependent CYP11A1 expression by competing for SRC-1 binding

Abstract: The orphan nuclear receptor LRH-1 (liver receptor homologue-1; NR5A2) plays a critical role in development, bile acid synthesis and cholesterol metabolism. LRH-1 is also expressed in the ovary where it is implicated in the regulation of steroidogenic genes for steroid hormone synthesis. In the present study, we investigated the molecular mechanisms of the transcriptional regulation of CYP11A1 by LRH-1 and found that LRH-1-mediated transactivation was markedly repressed by PIASy [protein inhibitor of activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…While SRC-1 stimulates, PIASy transrepresses LRH-1-dependent Cyp11a1 promoter activation. Although PIASy is an E3 SUMO-ligase, its transrepressive function does not seem to result from changes in the LRH-1 SUMOylation status [59]. In another study that investigated the transcriptional regulation of the Lrh-1 gene upon sphingosine-1-phosphate and prostaglandin E2 stimulation, it was shown that CCAAT/enhancer binding proteins d (C/EBPd) and the coactivators CREB-binding protein (CBP) and SRC-3 potentiate the interaction of cAMP response element binding protein (CREB) and LRH-1 [60].…”
Section: Srcsmentioning
confidence: 94%
See 1 more Smart Citation
“…While SRC-1 stimulates, PIASy transrepresses LRH-1-dependent Cyp11a1 promoter activation. Although PIASy is an E3 SUMO-ligase, its transrepressive function does not seem to result from changes in the LRH-1 SUMOylation status [59]. In another study that investigated the transcriptional regulation of the Lrh-1 gene upon sphingosine-1-phosphate and prostaglandin E2 stimulation, it was shown that CCAAT/enhancer binding proteins d (C/EBPd) and the coactivators CREB-binding protein (CBP) and SRC-3 potentiate the interaction of cAMP response element binding protein (CREB) and LRH-1 [60].…”
Section: Srcsmentioning
confidence: 94%
“…For example, stimulation of rat primary granulosa cells with pregnant mare serum gonadotropin (PMSG) leads to the SRC-1/LRH-1 transactivation of the inhibin alphasubunit gene, a gene that inhibits the release of folliclestimulating hormone (FSH) [10]. In the transcriptional regulation of the Cyp11a1 gene, SRC-1 and protein inhibitor of activated STAT (signal transducer and activator of transcription) y (PIASy) compete to bind LRH-1 [59]. While SRC-1 stimulates, PIASy transrepresses LRH-1-dependent Cyp11a1 promoter activation.…”
Section: Srcsmentioning
confidence: 99%
“…NR5A2 is involved in a variety of processes including ovulation and embryo differentiation and development (Fayard et al, 2004;Hsieh et al, 2009;Yazawa et al, 2010;Winkler et al, 2010). Hinshelwood et al (2005) found that NR5A2 plays a role in gonadal development, the initiation of folliculo genesis, and regulation of estrogen biosynthesis within the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin neuron-specific NR5A2 knockout mice (NR5A2 kiss-1-/-) have significantly reduced litter sizes (Atkin et al, 2013). In the ovary, NR5A2 regulates genes involved in follicular development, such as CYP11A1 (Hsieh et al, 2009); STAR (Taniguchi et al, 2009); HSD3B2 (Peng et al, 2003); INHA (Matulis and Mayo, 2012); and FDX1 (Imamichi et al, 2013). NR5A2 is expressed in the anterior pituitary, and regulates key genes underlying follicular development such as those encoding GnRHR (gonadotropin-releasing hormone receptor), LHR (luteinizing hormone receptor), and FSHR (follicle stimulating hormone receptor) (Zheng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analyses were performed as previously described [33]. The anti-Myc antibody was used to assess the expression of Myc-LRH-1, while anti-b-actin antibody determination of b-actin levels (Upstate Biotechnology) was used as a loading control.…”
Section: Western Blottingmentioning
confidence: 99%